Another night in the sun : live in Helsinki - Michael Monroe; Spin-Farm Oy (Spinefarm Records/ Michael Monroe Music, 2010)
15 kappaletta.
Keywords: Monroe, Michael, : 1962- : albumit; konsertit; laulajat; miehet; konserter (framträdanden); sångare; män; Suomi; Finland